Women and Gender in the Early Modern Low Countries, 1500-1750 - Moran, Sarah; Pipkin, Amanda (Brill, 2018)
Women were fundamental actors in early modern Low Countries society, playing major roles in the dynamic environment of economic, artistic, and cultural exchange of both the Catholic Southern Netherlands and the Protestant Dutch Republic.The Habsburg territories were governed by a string of women rulers. More ordinary Netherlandish women ran businesses, pursued careers as painters and writers, joined and led religious communities, and helped steer the course of debates between Protestants and Catholics. The wealthier among them were active in the financial markets and a number of them became highly influential patrons of art and architecture. Women of lesser means, on the other hand, might find themselves in difficult situations. At the same time, evolving traditions of the textual and visual representation of femininity reflected and shaped attitudes towards gender, and in turn impacted the lives of both women and men.